2019
DOI: 10.20944/preprints201904.0137.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recycling of Waste Cooking Oils: Variation of the Chemical Composition during Water Treatment

Abstract: Samples of sunflower Waste Cooking Oils (WCOs) subjected to several cycles of frying were treated with water under four different combinations of temperature and pH. The variation of the chemical composition of the oil samples was monitored through headspace Solid-Phase Microextraction (HS-SPME) coupled with gas-chromatographic technique (GC), 1H NMR spectroscopy and ESI+ mass spectrometry measurements. The possibility to modify the chemical composition of the recycled vegetable oil by tuning the water treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…On the other hand, one liter of waste vegetable oil poured into the environment can pollute 0.5 million liters of water, which will cause serious environmental problems [1][2][3][4]. Therefore, proper management of WCO is mandatory to reduce its impact on the global environment and improve their availability for reuse in various industrial processes such as bio-lubricants, biodiesel, asphalt additives and others.…”
Section: Main Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, one liter of waste vegetable oil poured into the environment can pollute 0.5 million liters of water, which will cause serious environmental problems [1][2][3][4]. Therefore, proper management of WCO is mandatory to reduce its impact on the global environment and improve their availability for reuse in various industrial processes such as bio-lubricants, biodiesel, asphalt additives and others.…”
Section: Main Materialsmentioning
confidence: 99%
“…A technology based on a combination of water treatment and filtration on porous materials was made in [4], designing a mini-recycling plant aimed at the production of biolubricants from WCO (Fig. 1) [4].…”
Section: Main Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the relative amounts of contamination produced during the cooking process are not increased. Research has shown that WCOs are very similar in chemical composition to the original cooking oils [49]. In recent years, increased interest in the processing of WCOs can be observed.…”
Section: Introductionmentioning
confidence: 99%